2022
DOI: 10.12688/amrcopenres.13105.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Covid-19 pandemic on hospices: A systematic integrated review and synthesis of recommendations for policy and practice

Abstract: Background: The Covid-19 pandemic resulted in the development of numerous recommendations for practice and policy for specialist palliative care provided by hospices in United Kingdom (UK), as hospices were significantly affected by the pandemic and protections put in place. The aim of this review is to identify and synthesise recommendations or implications for policy and practice that have been generated for adult hospice specialist palliative care during the first 24 months of the Covid-19 pandemic. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…10 In addition, findings from this study show that existing wraparound care models such as hospice did support some families well and therefore need to be better resourced to improve accessibility to a wider number of people. 8 Another key finding from this study was people's experiences of culturally-safe palliative and endof-life care during the pandemic. We identified that pandemic policies, such as visiting restrictions to institutional care settings, travel restrictions across borders and regions and limitations on attendance of funeral/tangihanga restrictions, disproportionately impacted Indigenous and families from minoritised ethnic groups.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…10 In addition, findings from this study show that existing wraparound care models such as hospice did support some families well and therefore need to be better resourced to improve accessibility to a wider number of people. 8 Another key finding from this study was people's experiences of culturally-safe palliative and endof-life care during the pandemic. We identified that pandemic policies, such as visiting restrictions to institutional care settings, travel restrictions across borders and regions and limitations on attendance of funeral/tangihanga restrictions, disproportionately impacted Indigenous and families from minoritised ethnic groups.…”
Section: Discussionmentioning
confidence: 80%
“…21,22 Lack of access to and availability of specialist bereavement care have been identified as barriers in a number of countries. 8 Particular concerns have been raised regarding the increased risk of complex grief among minoritised ethnic communities who have died at higher rates from COVID-19. 23,24 Indeed, while there has been a widespread acknowledgment that the pandemic has exacerbated inequities around health care for Indigenous, migrant and ethnically minoritised communities, 25 very less empirical research relates to endof-life care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly pronounced in the ways that compromises in care – such as delaying care and waiting – were experienced as emotionally and practically necessary at the time. 17 …”
Section: What Social and Cultural Issues Are Shaping Pandemic Delay?mentioning
confidence: 99%